ANTIBIOTIC RESISTANCE OF HELICOBACTER PYLORI ISOLATES FROM KAZAKH PATIENTS - Kulmambetova , G.N.; Bekenova , E.E.; Tujakova , A.K.; Kozhakhmetov , S.S.; Logvinenko , A.A.; Sukashev , A.T.; Almagambetov , K.K. (Eurasian Journal of Applied Biotechnology, 2015)
Helicobacter pylori strains can be resistant to important triple combination therapies for H. pylori eradication. The aim of this study was to investigate the rate of resistance to clarithromycin, metronidazole, amoxicillin, tetracycline, and rifampicin, as well as to detect antibiotic resistance-associated mutations in H. pylori isolates from patients in Kazakhstan. Susceptibility of 20 H. pylori strains was tested using the E test method. Genes associated with resistance and susceptible clinical isolates were sequenced in order to assess resistance and non-resistance associated genetic alterations. Of the 20 clinical isolates examined, 8 (40%) showed phenotypic resistance to metronidazole (MIC > 256 mg/L), 13 (65%) to clarithromycin (MIC > 256 mg/L), and 1 (5%) to amoxicillin (MIC > 6 mg/L). The majority of resistant strains had point mutations in the 23S rRNA gene and rdxA gene, and one strain had mutations in the pbp1A gene. The remaining isolates with moderate resistant isolates (MIC <0.016 mg/L) demonstrated a drug-susceptible phenotype, and did not harbour any mutation in the gene sequences evaluated. In the Kazakh population of existing clarithromycin and metronidazole resistance, tetracycline, amoxicillin, and rifampicin could prove useful for rescue regimens in patients with previously unsuccessful H. pylori eradication regimens.